"KYDS": an innovative service addressing the health needs of youth and families in an Australian community. (April 2013) - Citer, David; Carlson, Kym; McClellan, Danni; McGaw, Pam; Walter, Sophie; Bennett, David; Walter, Garry
Objective: To describe the evolution of KYDS Youth Development Service ("KYDS"), a pioneering youth service in Sydney, Australia, its range of programs and the challenges that it has faced. Conclusions: KYDS emerged in the context of the escalating presentation of mental health and other problems affecting young people, and the desire of a local community to provide a service for its youth. The service has expanded since opening in 2005 and now includes, among other elements, therapy for referred clients, parent educational forums, and group programs such as a young women's program and a program for teenagers with parents affected by mental illness. The challenges for the service include financial pressures, service expansion, and how to best complement other services in the public and private sector.